2015
DOI: 10.1002/art.39408
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, Functional, and Gene Expression Profiling of Peripheral CD45RA+ and CD45RO+ CD4+CD25+CD127low Treg Cells in Patients With Chronic Rheumatoid Arthritis

Abstract: ObjectiveConflicting evidence exists regarding the suppressive capacity of Treg cells in the peripheral blood (PB) of patients with rheumatoid arthritis (RA). The aim of this study was to determine whether Treg cells are intrinsically defective in RA.MethodsUsing a range of assays on PB samples from patients with chronic RA and healthy controls, CD3+CD4+CD25+CD127low Treg cells from the CD45RO+ or CD45RA+ T cell compartments were analyzed for phenotype, cytokine expression (ex vivo and after in vitro stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 52 publications
6
39
1
Order By: Relevance
“…Regarding T regs , as expected [18] there was a slightly higher percentage of CD25 + CD127 low T cells within the CD4 + CD45RO + T cell population (on average 10%) when compared to CD4 + CD45RA + or total CD4 + T cells (on average 5 and 7%, respectively), but the frequencies between the groups were not statistically significantly different ( Fig. 2b and data not shown).…”
Section: Similar Frequencies Of Major Immune Cell Subsets In Periphersupporting
confidence: 78%
“…Regarding T regs , as expected [18] there was a slightly higher percentage of CD25 + CD127 low T cells within the CD4 + CD45RO + T cell population (on average 10%) when compared to CD4 + CD45RA + or total CD4 + T cells (on average 5 and 7%, respectively), but the frequencies between the groups were not statistically significantly different ( Fig. 2b and data not shown).…”
Section: Similar Frequencies Of Major Immune Cell Subsets In Periphersupporting
confidence: 78%
“…Unfortunately, studies of peripheral blood T cells in RA have often yielded inconsistent results. For example, the abundance of regulatory T cells (T REG ) in RA peripheral blood has been observed to be reduced or expanded compared to healthy controls in different studies [3337]; in addition, conflicting results have been reported concerning the suppressive capability of T reg cells in RA [3842]. Inconsistent results can be partially attributed to variation in markers used across different studies or the difficulty of resolving highly heterogeneous populations with bulk cell assays – which advancing single cell technologies might help to obviate.…”
Section: Low-dimensional Single Cell Analysis Of T Cells In Ramentioning
confidence: 99%
“…However, studies on Tregs phenotype and function in RA patients have yielded conflicting results: some studies found a decrease in Tregs in peripheral blood from RA patients; 12,13 whereas others did not. 14,15 In experimental models of arthritis, Tregs have been shown to inhibit OC formation and activity. 16 These data have been confirmed by our group in humans as well, during periprosthetic osteolysis.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%